POTENSI KOMBINASI EKSTRAK ETANOL DAUN DADAP SEREP (Erythrina subumbrans) DAN PEGAGAN (Centella asiatica) DALAM MENURUNKAN RISIKO DISFUNGSI ENDOTEL PADA TIKUS DENGAN DIET TINGGI FRUKTOSA - Kaniawati, Marita; Sulaeman, Agus; Nurfazri Istiqomah, Aulia; Efraim Lian, Kevin (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Fructose has long been known as a sugar additive or sweetener, commonly found in soft drinks, pastries, and other processed foods. High levels of added sugar in the daily diet increase the risk of various metabolic disorders, including insulin resistance. Insulin resistance can lead to impaired endothelial function (endothelial dysfunction), which can lead to impaired vasodilation responses. Endothelial dysfunction can lead to an increased risk of cardiovascular diseases such as atherosclerosis, coronary heart disease (CHD), hypertension, and other vascular diseases. The aim of this study was to identify the potential of a combination of dadap serep (Erythrina subumbrans) and pegagan (Centella asiatica) to reduce the risk of endothelial dysfunction (as measured by nitric oxide (NO) levels) triggered by high fructose consumption. This research method is an in vivo experimental preventive using 36 rats divided into normal group, induction group, comparison group of curcumin 9 mg/kgBW, test group 1 EEPDS 50:100 mg/kgBW, test group 2 EEPDS 100:100 mg/kgBW and test group 3 EEPDS 100:50 mg/kgBW. Measurement of NO levels using the Griess method, while insulin resistance examination was carried out using the insulin tolerance test method. The results showed that the combination group of EEPDS 100:50 mg/kgBW was the group that showed the most optimal effect in maintaining endothelial function and had the best insulin sensitivity. The conclusion of this study shows that the combination of EEPDS 100:50 mg/kgBW is effective in maintaining insulin sensitivity and maintaining endothelial function in rats.